EVALUASI TINGKAT EFISIENSI PEMANFAATAN RUANG DI GEDUNG PUSAT UNIVERSITAS GADJAH MADA - , Nunu Lutfi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to evaluate the efficiency of work space utilization, work facilities, as well as in the assembly room utilization of Universitas Gadjah Mada head office. This study uses secondary data obtained from the Universitas Gadjah Mada Directorate of Development and Planning Administration and Household Administration. This study used a descriptive analysis to describe and explain the data on study phenomenonâs to assess and analyze the assets management of as spaces, office facilities and assembly room in the Universitas Gadjah Mada head office. The research found that the work space utilization are not optimal or even overload. This happens because there is no work spaceâs utilization standard and perception differences in the management and the utilization of the existing work space between the units in the head office of Universitas Gadjah Mada so that there is impression of ignorance the efficiency and optimization of work space. From the aspect of infrastructure, in general all the room meets the standards prescribed by the Minister of Home Affairs Regulation No. 7 of 2006 on Standards for Local Government facilities. Meanwhile, on the utilization frequency of the assembly room has been stated good since the total utilization rate reached 69,06 percent respectively, Ruang Sidang SA (106,7 percent), Ruang Sidang LPPM (99,17 percent), Ruang Sidang I (91,6 percent), Ruang Multimedia (82,5 percent), Ruang Sidang DPPA (59,17 percent), Ruang sidang WMA (49,17 percent), Balai Senat (33,3 percent) and Ruang Serbaguna DPPA (30,83 percent).